Pharmacist Intervention in Fluvoxamine Induced Alopecia: A Case Report in Tertiary Care Teaching Hospital - Koshy, Benson; Hosur, Shashank S; Jose, Stimson; Rajashekarachar, Yogananda; Das, Gopal (Indian Journal of Pharmacy Practice)
Hair loss (alopecia) is an occasional side effect associated with psychotropic drugs use. Fluvoxamine is a synthetic antidepressant which acts as a selective serotonin reuptake inhibitor as well as sigma-1 receptor agonist. Psychotropic drugs are considered to cause hair loss by affecting the telogenic phase of hair follicle. Here we present a case of a 28 year old male patient reported with diffuse hair loss after administration of fluvoxamine and condition remitted after cessation of the drug. Our report suggests the possibility of developing alopecia with fluvoxamine use.
Keywords: Fluvoxamine; Adverse effect; Alopecia; Naranjo Causality assessment scale; Drug intervention; Clinical improvement